Peningkatan Motivasi Belajar Bahasa Inggris dengan Memanfaatkan Aplikasi Media Sosial di MA Darussalam Barandasi - Tanasy, Novalia; Wahab, Isnaeni; Nashruddin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muslim Maros, 2025)
English is often perceived as a difficult and boring subject, which can lead students to become indifferent and unmotivated to learn it. This issue is also prevalent among the students of class III IPS at MA Darussalam Barandasi. On the other hand, spending time on social media platforms like TikTok, Instagram, and Snapchat is one of their favorite pastimes. These students often spend hours on these platforms daily, with little to no benefit for their studies. A team of lecturers from the English Education Department and students from the KEMAL program at FKIP Universitas Muslim Maros recognized this as a problem that needed a solution. A creative and effective approach was required—one that could combine both interests into a meaningful and beneficial activity. As a result, a service program was developed with the aim of boosting students’ motivation to learn English through the use of social media applications. The outcomes of this initiative were very promising. Students responded positively, with enthusiasm and excitement, to the idea of learning English via social media. They began following several educational accounts, carefully engaging with content related to English learning materials. This content was then studied and practiced effectively. Students also agreed that using social media made English learning sessions more enjoyable, which in turn motivated them to engage with the subject with greater enthusiasm.